Sexual Orientation, Parental Support, and Health During the Transition to Young Adulthood - Needham, Belinda L; Austin, Erika L (Journal of youth and adolescence)
Some recent studies suggest that sexual minorities may have worse health-related outcomes during adolescence because they report lower levels of family connectedness, a key protective resource. Using data from wave 3 of the National Longitudinal Study of Adolescent Health (n = 11,153; 50.6% female; mean age = 21.8 years), this study extends prior research on adolescents to young adults. We examine whether lesbian, gay, and bisexual (LGB) young adults report lower levels of parental support than their heterosexual peers and whether differences in parental support help explain why LGB young adults tend to have worse health-related outcomes. We find that lesbian and bisexual women report lower levels of parental support than heterosexual women and that gay men report lower levels of parental support than bisexual and heterosexual men. Compared to heterosexual women, lesbian and bisexual women have higher odds of suicidal thoughts and recent drug use; bisexual women also have higher odds of elevated depressive symptomatology and heavy drinking. Gay men have higher odds of suicidal thoughts than heterosexual men. With the exception of heavy drinking, parental support either partially or fully mediates each of the observed associations. Even though the transition from adolescence to young adulthood is characterized by increased independence from parents, parental support remains an important correlate of health-related outcomes during this stage of life. Sexual minorities report lower levels of parental support during young adulthood, which helps explain why they have worse health-related outcomes. Interventions designed to strengthen relationships between LGB young adults and their parents could lead to a reduction in health disparities related to sexual orientation.